Moving on: Transition experiences of young adults with chronic pain - Andrea Higginson; Paula Forgeron; Denise Harrison; G. Allen Finley; Bruce D. Dick (Taylor & Francis Group, 2019)
Purpose The purpose of this study was to explore the transition experience of young adults with chronic pain in Canada from the pediatric health care setting to the adult health care setting. Materials and Methods A qualitative descriptive approach using semistructured interviews was used to capture the transition experiences of young people with chronic pain who have recently transferred from the pediatric setting to the adult health care setting. Participants were recruited from west, central, and the east coast of Canada to situate the findings within the context of Canada. Interviews were transcribed and analyzed using qualitative inductive content analysis. Results Nine participants were interviewed, three from each part of Canada (west, central, and east). Five common categories were determined to describe the transition experience of young adults with chronic pain which include (1) independence (I can do it, maybe?), (2) pain trajectory (stress and pain along for the ride), (3) social support networks (need a shoulder to lean on), (4) parental support (obviously they are there), and (5) collaborative systems (the bridge). Conclusion Young people with chronic pain experience unique challenges when faced with transitioning to the adult health care setting. Supporting the young person and his or her family in preparation and readiness and collaboration between the pediatric and adult health care settings are essential to ensure a smooth transition and avoid negative transition outcomes. Further research is needed to determine the best ways to prepare young people for transition and the care activities required in both pediatric and adult health care settings to improve pain-related outcomes posttransition.